Ecological Studies in the Antarctic Sea Ice Zone 2002
DOI: 10.1007/978-3-642-59419-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour of Weddell seals, and its ecological implications

Abstract: Time-depth recorder data of eight adult Weddell seals (Leptonychotes weddellii) provided simultaneous dive records over 8 days in the Drescher Inlet, eastern Weddell Sea coast, in February 1998. The seals primarily foraged within two depth layers, these being from the sea surface to 160 m where temperature and salinity varied considerably, and near the bottom from 340 to 450 m where temperature was lowest and salinity highest. While both pelagic and benthic diving occurred during daylight, the seals foraged al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 14 publications
6
63
0
Order By: Relevance
“…Therefore dives to 50-100 m observed in this study might correspond to foraging dives focused on benthos. This is consistent with the suggestion of Plötz et al (2001) that Weddell seals might primarily forage within 2 depth layers. Plötz et al (2001) suggested that Weddell seals might prefer to forage deeper during daylight and shallower during darkness, and that the diurnal pattern in dive depth might be finely tuned to vertically migrating prey (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore dives to 50-100 m observed in this study might correspond to foraging dives focused on benthos. This is consistent with the suggestion of Plötz et al (2001) that Weddell seals might primarily forage within 2 depth layers. Plötz et al (2001) suggested that Weddell seals might prefer to forage deeper during daylight and shallower during darkness, and that the diurnal pattern in dive depth might be finely tuned to vertically migrating prey (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…2), with high frequencies of shallow dives to depths less than 50 m. Deep dives were concentrated around 100 m for seals AF4, JM5 and JF6. One adult male (AM2) and one adult female (AF3) displayed high numbers of deep dives to depths [200 m, while the remaining seal (AM1) concentrated its dives at depths between 100 and 150 m. The bimodal patterns of dive depths are similar to that reported for seals tagged at the Drescher Inlet (Plötz et al 2001), although seals there targeted deeper water layers close to the seafloor in the region of 400 m, where evidence for foraging (based on jaw movement data) was also reported by Liebsch et al (2007). Seals AM1, AF4, JM5 and JF6 displayed increased bottom times when diving to similar depths, compared to the depths they most often dived to (Fig.…”
Section: Divessupporting
confidence: 69%
“…This can likely be explained by potential prey species occurring in more concentrated numbers within preferred temperature layers when there is more stratification in temperature through the water column, whereas prey species are more likely to be scattered in the water column when the temperature structure is relatively well mixed (Takahashi et al 2008). Indeed, the vertical distribution of Pleuragramma antarcticum, a known prey species of Weddell seals, was associated closely with the vertical structure of the water column when a clear pycnocline was present (Plötz et al 2001). Seals may therefore take advantage of increased concentrations of prey by maximising their forage effort in appropriate depth layers.…”
Section: Environmental Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors have been glued to the jaw of the seal that detect opening of the mouth (Bornemann et al, 1992;Plötz et al, 2001), but prey capture may be diffi cult to distinguish from other jaw movements during social behavior (e.g., threats and bites). Temperature-transmitting thermistors have been introduced into the stomach to monitor changes in the temperature of stomach contents associated with ingestion of cold items, such as ectothermic fi sh ( Bornemann, 1994;Hedd et al, 1996;Austin et al, 2006aAustin et al, , 2006bKuhn and Costa, 2006).…”
Section: Monitoring Food Consumption During the Lactation Periodmentioning
confidence: 99%